Eighteen months of depression: examining the chronic care management of depression with particular reference to Pacific people - Tutty S; Goodyear-Smith F (CSIRO Publishing, 2014)
INTRODUCTION: Primary care is responsible for the 17% of the population with mild to moderately severe mental illness. Total Healthcare Otara (THO), with 49% of its patients of Pacific ethnicity, presents an opportunity to study the primary care management of depression, inclusive of Pacific people. While it had been assumed that Pacific people in New Zealand suffer less mental illness, Te Rau Hinengaro: The New Zealand Mental Health Survey showed this is not the case. AIM: The aim of the study was to examine a Chronic Care Management (CCM) programme for depression in a predominantly Pacific practice. METHODS: A clinical audit of the CCM depression programme used by THO between 31 March 2009 and 30 September 2010. Participants were patients aged 18-64 years who scored ≥15 on the Patient Health Questionnaire-9 (PHQ-9). Computer templates completed for each consultation, including serial PHQ-9s, were analysed over time and across different ethnic groups. RESULTS: Cook Island Maori patients participated in the CCM depression programme in proportionally greater numbers than their enrolment in THO, while Samoan and Tongan patients participated significantly less. The mean PHQ-9 score fell rapidly over the first few visits and then levelled off, without reaching the normal range. Dropout rate was 60% after the third consultation irrespective of ethnicity or gender. DISCUSSION: There is a need for ethnic-specific research into depression in Pacific ethnic groups. A significant immediate improvement in PHQ-9 on entering the CCM depression programme suggests enrolment is therapeutic. However, further research into the CCM depression programme is needed, particularly the reasons for non-attendance.